Christmas Forever (The Inn at Sunset Harbor-Book 8) - Sophie, Love (Lukeman Literary, 2017)
"Sophie Love's ability to impart magic to her readers is exquisitely wrought in powerfully evocative phrases and descriptions....This is the perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (Diane Donovan re For Now and Forever) CHRISTMAS FOREVER is book #8-and the finale-in the #1 bestselling romance series THE INN AT SUNSET HARBOR, which begins with For Now and Forever (book #1)-a free download! Winter is coming in Sunset Harbor, and Emily Mitchell is nearing her third trimester. While they continue to develop their new private island, a new opportunity arises-one Emily had never anticipated, and which could change everything. Roy's time left to live is running out fast, and as Christmas looms and all are busy preparing, Emily knows that this will be the most meaningful one of her life. It will be a holiday season that changes all of their lives forever. CHRISTMAS FOREVER is book #8 in a dazzling new romance series that will make you laugh, cry, keep you turning pages late into the night-and make you fall in love with romance all over again. Sophie's new romance series, LOVE LIKE THIS, is now also available! "A very well written novel, describing the struggle of a woman (Emily) to find her true identity. The author did an amazing job with the creation of the characters and her description of the environment. The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews, Roberto Mattos (re For Now and Forever)
Keywords: Romantika, romány pro ženy